Understanding user emotions through interaction with persuasive technology - Wan Nooraishya Wan Ahmad; Ali, N.M.; Ahmad Rodzuan, A.R. (Science and Information Organization, 2020)
Emotions play a vital role in persuasion; thus, the use of persuasive applications should affect and appeal to the users' emotions. However, studies in persuasive technology have yet to discover what triggered the users' emotions. Therefore, the objectives of this study are to examine user emotions and to identify the factors that affect user emotions in using persuasive applications. This study is conducted in three stages; preinteraction, during-interaction and post-interaction, employed a mixed-method approach using Geneva Emotions Wheel (GEW) and open-ended survey questions that analyzed using thematic analysis. The result shows that most of the emotions that users felt belong to high-control positive valence emotions that consist of interest, joy and pleasure. User, system and interaction are the three factors that triggered the emotions encompasses of elements such as Individual Awareness, Personality, Interface Design, Persuasive Function, Content Presentation, System Quality, Usability, and Tasks. The findings contribute to the body knowledge of Persuasive Technology, where the discovered factors and its elements are the antecedents that should be the concern in constructing an emotion-based trust design framework that could bring emotional impact to users to ensure a successful persuasion. © 2020, Science and Information Organization.